Synthesis and In Vivo Evaluation of Insulin-Loaded Whey Beads as an Oral Peptide Delivery System - Joanne Heade; Fiona McCartney; Miguel Chenlo; Olga Moreno Marro; Maja Severic; Robert Kent; Sinead B. Bleiel; Clara V. Alvarez; Brendan T. Griffin; David J. Brayden (MDPI AG, 2021)
For many diabetics, daily, lifelong insulin injections are required to effectively manage blood glucose levels and the complications associated with the disease. This can be a burden and reduces patient quality of life. Our goal was to develop a more convenient oral delivery system that may be suitable for insulin and other peptides. Insulin was entrapped in 1.5-mm beads made from denatured whey protein isolate (dWPI) using gelation. Beads were then air-dried with fumed silica, Aerosil®. The encapsulation efficiency was ~61% and the insulin loading was ~25 µg/mg. Dissolution in simulated gastric-, and simulated intestinal fluids (SGF, SIF) showed that ~50% of the insulin was released from beads in SGF, followed by an additional ~10% release in SIF. The omission of Aerosil® allowed greater insulin release, suggesting that it formed a barrier on the bead surface. Circular dichroism analysis of bead-released insulin revealed an unaltered secondary structure, and insulin bioactivity was retained in HepG2 cells transfected to assess activation of the endogenous insulin receptors. Insulin-entrapped beads were found to provide partial protection against pancreatin for at least 60 min. A prototype bead construct was then synthesised using an encapsulator system and tested in vivo using a rat intestinal instillation bioassay. It was found that 50 IU/kg of entrapped insulin reduced plasma glucose levels by 55% in 60 min, similar to that induced by subcutaneously (s.c.)-administered insulin (1 IU/kg). The instilled insulin-entrapped beads produced a relative bioavailability of 2.2%. In conclusion, when optimised, dWPI-based beads may have potential as an oral peptide delivery system.